The Short Version of IPIP-BFM Scale Properties Based on Bugis-Makassar Cultural Background: Do the Items Match with Javanese Culture? - Syahrul Alim; Titin Florentina Purwasetiawatik; A. Nur Aulia Saudi; Susi Susanti (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
Cultural difference is one of the elements that form individuals. It corresponds with attitudes and beliefs that influence human cognition and behavior. As a response, it is essential to study cultural differences to develop an appropriate measurement tool. This study aims to (1) evaluate the psychometric properties of the IPIP-BFM short version scale based on the Bugis-Makassar cultural setting and also (2) compare with Javanese cultural background results. A total of 430 students participated (78% women and 22% men). We observed that the Item-total correlation ranged from 0.51 to 0.74, with reliability coefficient: intellectual (0.85); consciousness (0.85); extraversion (0.85); agreeableness (0.79); and neuroticism (0.89). The Kaiser Meyer-Olkin was 0.87, and the Bartlett Test of Sphericity was 5191,3 (p < 0.01). All the items had a factor loading >0.60; variance explained 63,1 (63%) and clear factorial structures. The short version scale had good psychometric properties. Meanwhile, the items comparison of the two measurement tools from both cultural backgrounds reveals that two-item were the same in factors: intellectual, extraversion, and emotional, while four items were in consciousness. However, on the agreeableness factor, all items were the same. It shows that cultural variations indeed affect an individual's perception of an item.